An effective Pd nanocatalyst in aqueous media: stilbene synthesis by Mizoroki–Heck coupling reaction under microwave irradiation - García, Carolina S.; Uberman, Paula M.; Martín, Sandra E. (Beilstein Journal of Organic Chemistry, 2017)
Aqueous Mizoroki–Heck coupling reactions under microwave irradiation (MW) were carried out with a colloidal Pd nanocatalyst stabilized with poly(N-vinylpyrrolidone) (PVP). Many stilbenes and novel heterostilbenes were achieved in good to excellent yields starting from aryl bromides and different olefins. The reaction was carried out in a short reaction time and with low catalyst loading, leading to high turnover frequency (TOFs of the order of 100 h−1). The advantages like operational simplicity, high robustness, efficiency and turnover frequency, the utilization of aqueous media and simple product work-up make this protocol a great option for stilbene syntheses by Mizoroki–Heck reaction.
Keywords: aqueous reaction medium; MAOS; Mizoroki–Heck reaction; Pd nanoparticle; sustainable organic synthesis

(untitled) - Beletskaya, I. P.; Cheprakov, A. V. (Chem. Rev., 2000)

Metal-Catalyzed Cross-Coupling Reaction - De Meijere, A.; Diederich, F. (Wiley-VCH Verlag GmbH, 2008)

RSC Catalysis Series Nº 21 - Colacot, T. (New Trends in Cross-Coupling: Theory and Applications, 2015)

(untitled) - Zhang, N.; Xu, Y.-J. (Chem. Mater., 2013)

(untitled) - Wu, X.-F.; Anbarasan, P.; Neumann, H.; Beller, M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Kumar, A.; Rao, G. K.; Kumar, S.; Singh, A. K. (Organometallics, 2014)

(untitled) - Alonso, F.; Beletskaya, I. P.; Yus, M. (Tetrahedron, 2005)

(untitled) - Le Bras, J.; Muzart, J. (Chem. Rev., 2011)

(untitled) - Mc Cartney, D.; Guiry, P. J. (Chem. Soc. Rev., 2011)

(untitled) - Patel, H. H.; Sigman, M. S. (J. Am. Chem. Soc., 2015)

The Mizoroki-Heck Reaction - Oestreich, M. (John Wiley & Sons, Ltd, 2009)

(untitled) - Liu, X.; Li, B.; Gu, Z. (J. Org. Chem., 2015)

The Mizoroki-Heck Reaction - Oestreich, M.; Beletskaya, I. P.; Cheprakov, A. V. (John Wiley & Sons Ltd, 2009)

(untitled) - De Meijere, A.; von Zezschwitz, P.; Bräse, S. (Acc. Chem. Res., 2005)

(untitled) - Shibasaki, M.; Vogl, E. M.; Ohshima, T. (Adv. Synth. Catal., 2004)

(untitled) - Nicolaou, K. C.; Bulger, P. G.; Sarlah, D. (Angew. Chem., Int. Ed., 2005)

(untitled) - Abbas, S.; Ferris, L.; Norton, A. K.; Powell, L.; Robinson, G. E.; Siedlecki, P.; Southworth, R. J.; Stark, A.; Williams, E. G. (Org. Process Res. Dev., 2008)

(untitled) - Raggon, J. W.; Snyder, W. M. (Org. Process Res. Dev., 2002)

(untitled) - Yu, L.; Huang, Y.; Wei, Z.; Ding, Y.; Su, C.; Xu, Q. (J. Org. Chem., 2015)

Nanomaterials in Catalysis - Serp, P.; Philippot, K. (Wiley-VCH Verlag & Co. KGaA, 2013)

Nanocatalysis - Heinz, U.; Landman, U. (Springer, 2007)

(untitled) - Peral, D.; Gómez-Villarraga, F.; Sala, X.; Pons, J.; Carles Bayón, J.; Ros, J.; Guerrero, M.; Vendier, L.; Lecante, P.; García-Antón, J.; Philippot, K. (Catal. Sci. Technol., 2013)

(untitled) - Molnár, Á. (Chem. Rev., 2011)

(untitled) - Astruc, D. (Inorg. Chem., 2007)

(untitled) - Bej, A.; Ghosh, K.; Sarkar, A.; Knight, D. W. (RSC Adv., 2016)

(untitled) - Isfahani, A. L.; Mohammadpoor-Baltork, I.; Mirkhani, V.; Khosropour, A. R.; Moghadam, M.; Tangestaninejad, S.; Kia, R. (Adv. Synth. Catal., 2013)

(untitled) - Shen, C.; Shen, H.; Yang, M.; Xia, C.; Zhang, P. (Green Chem., 2015)

(untitled) - Elazab, H. A.; Siamaki, A. R.; Moussa, S.; Gupton, B. F.; El-Shall, M. S. (Appl. Catal., A, 2015)

(untitled) - Camp, J. E.; Dunsford, J. J.; Dacosta, O. S. G.; Blundell, R. K.; Adams, J.; Britton, J.; Smith, R. J.; Bousfield, T. W.; Fay, M. W. (RSC Adv., 2016)

(untitled) - Ngnie, G.; Dedzo, G. K.; Detellier, C. (Dalton Trans., 2016)

(untitled) - Gniewek, A.; Trzeciak, A. M.; Ziółkowski, J. J.; Kępiński, L.; Wrzyszcz, J.; Tylus, W. (J. Catal., 2005)

(untitled) - Durap, F.; Metin, Ö.; Aydemir, M.; Özkar, S. (Appl. Organomet. Chem., 2009)

(untitled) - Strappaveccia, G.; Ismalaj, E.; Petrucci, C.; Lanari, D.; Marrocchi, A.; Drees, M.; Facchetti, A.; Vaccaro, L. (Green Chem., 2015)

(untitled) - Song, K.; Liu, P.; Wang, J.; Pang, L.; Chen, J.; Hussain, I.; Tan, B.; Li, T. (Dalton Trans., 2015)

(untitled) - Fernández-García, L.; Blanco, M.; Blanco, C.; Álvarez, P.; Granda, M.; Santamaría, R.; Menéndez, R. (J. Mol. Catal. A: Chem., 2016)

(untitled) - Martins, D. D. L.; Alvarez, H. M.; Aguiar, L. C. S.; Antunes, O. A. C. (Appl. Catal., A, 2011)

(untitled) - Baig, R. B. N.; Varma, R. S. (Chem. Soc. Rev., 2012)

(untitled) - Gawande, M. B.; Bonifácio, V. D. B.; Luque, R.; Branco, P. S.; Varma, R. S. (Chem. Soc. Rev., 2013)

(untitled) - Li, C.-J.; Chen, L. (Chem. Soc. Rev., 2006)

(untitled) - Prat, D.; Wells, A.; Hayler, J.; Sneddon, H.; McElroy, C. R.; Abou-Shehada, S.; Dunn, P. J. (Green Chem., 2016)

(untitled) - Dindulkar, S. D.; Jeong, D.; Kim, H.; Jung, S. (Carbohydr. Res., 2016)

(untitled) - Bahadorikhalili, S.; Ma’mani, L.; Mahdavi, H.; Shafiee, A. (RSC Adv., 2015)

(untitled) - Potier, J.; Menuel, S.; Rousseau, J.; Tumkevicius, S.; Hapiot, F.; Monflier, E. (Appl. Catal., A, 2014)

(untitled) - Gawande, M. B.; Shelke, S. N.; Zboril, R.; Varma, R. S. (Acc. Chem. Res., 2014)

(untitled) - Arvela, R. K.; Leadbeater, N. E. (J. Org. Chem., 2005)

(untitled) - Uberman, P. M.; Pérez, L. A.; Lacconi, G. I.; Martín, S. E. (J. Mol. Catal. A: Chem., 2012)

(untitled) - Uberman, P. M.; Pérez, L. A.; Martín, S. E.; Lacconi, G. I. (RSC Adv., 2014)

(untitled) - Uberman, P. M.; García, C. S.; Rodríguez, J. R.; Martín, S. E. (Green Chem., 2017)

(untitled) - Kou, J.; Bennett-Stamper, C.; Varma, R. S. (ACS Sustainable Chem. Eng., 2013)

(untitled) - Li, X.; Zhao, X.; Gao, S.; Marqués-González, S.; Yufit, D. S.; Howard, J. A. K.; Low, P. J.; Zhao, Y.; Gan, N.; Guo, Z. (J. Mater. Chem. A, 2013)

(untitled) - Jiang, Z.-j.; Wang, W.; Zhou, R.; Zhang, L.; Fu, H.-y.; Zheng, X.-l.; Chen, H.; Li, R.-x. (Catal. Commun., 2014)

(untitled) - Shah, D.; Kaur, H. (J. Mol. Catal. A: Chem., 2016)

(untitled) - Oberholzer, M.; Gerber, R.; Frech, C. M. (Adv. Synth. Catal., 2012)

(untitled) - Xu, T.; Zhang, Q.; Jiang, D.; Liang, Q.; Lu, C.; Cen, J.; Li, X. (RSC Adv., 2014)

(untitled) - Planellas, M.; Moglie, Y.; Alonso, F.; Yus, M.; Pleixats, R.; Shafir, A. (Eur. J. Org. Chem., 2014)

(untitled) - Itami, K.; Nokami, T.; Ishimura, Y.; Mitsudo, K.; Kamei, T.; Yoshida, J.-i. (J. Am. Chem. Soc., 2001)

(untitled) - Jeffery, T.; Ferber, B. (Tetrahedron Lett., 2003)

(untitled) - Gordillo, A.; de Jesús, E.; López-Mardomingo, C. (Chem. Commun., 2007)

Stilbenes: Applications in Chemistry, Life Sciences and Materials Science - Likhtenshtein, G. (2009)

(untitled) - Albert, S.; Horbach, R.; Deising, H. B.; Siewert, B.; Csuk, R. (Bioorg. Med. Chem., 2011)

(untitled) - Chalal, M.; Vervandier-Fasseur, D.; Meunier, P.; Cattey, H.; Hierso, J.-C. (Tetrahedron, 2012)

(untitled) - Ferré-Filmon, K.; Delaude, L.; Demonceau, A.; Noels, A. F. (Coord. Chem. Rev., 2004)

(untitled) - Kappe, C. O. (Chem. Soc. Rev., 2013)

(untitled) - Alacid, E.; Nájera, C. (J. Org. Chem., 2009)

(untitled) - Guastavino, J. F.; Budén, M. E.; Rossi, R. A. (J. Org. Chem., 2014)

(untitled) - Cui, X.; Li, Z.; Tao, C.-Z.; Xu, Y.; Li, J.; Liu, L.; Guo, Q.-X. (Org. Lett., 2006)

(untitled) - Lu, C.; Guo, Y.; Li, J.; Yao, M.; Liao, Q.; Xie, Z.; Li, X. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Gordillo, A.; Forigua, J.; López-Mardomingo, C.; de Jesús, E. (Organometallics, 2011)

(untitled) - Diéguez, H. R.; López, A.; Domingo, V.; Arteaga, J. F.; Dobado, J. A.; Herrador, M. M.; Quílez del Moral, J. F.; Barrero, A. F. (J. Am. Chem. Soc., 2010)